Clinical study of traditional Chinese medicine comprehensive therapy for Exercise-Related musculoskeletal injuries using musculoskeletal ultrasound observation - Lixia Yuan; Juan Shi; Xiaoli Liu; Sheng Wang; Lianghong Li (Journal of Orthopaedic Surgery and Research)
Abstract Background This study aimed to compare the clinical efficacy of Jingshang Gao in the treatment of lateral ankle sprains by observing the healing process with musculoskeletal ultrasound. Methods We enrolled 90 patients with lateral ankle sprains who were admitted to our hospital from July 1, 2022, to July 1, 2023. The average age was 36.21 years, and 35 patients were male (38.9%). Patients were divided into two groups based on different treatment methods: the control group received oral celecoxib capsules(200 mg once daily), and the research group received Jingshang Gao topical application. We compared the basic data between the two groups. Results In terms of pain score, both groups had lower VAS scores at T1-T4 than at T0, and the research group had significantly lower VAS scores than the control group at T3 and T4 (p < 0.01, Cohen’s d = 0.82). In terms of functional score, both groups had higher Kaikkonen ankle injury function scores at T1-T4 than at T0, and the research group had significantly higher scores than the control group at T3 and T4 (p < 0.01, Cohen’s d = 0.87). In terms of AOFAS score, the research group had significantly higher functional scores than the control group (94.307 ± 18.206 vs. 81.216 ± 17.22, p < 0.001, Cohen’s d = 0.75). Musculoskeletal ultrasound showed that the healing rate of the ligament in the research group was 82.2% (95% CI: 71.1–93.3%), which was significantly higher than the control group’s 57.8% (95% CI: 43.3–72.3%), p = 0.011. In terms of SF-36 score, the research group had a higher VT score than the control group (75.6 ± 9.2 vs. 68.4 ± 8.9, p = 0.024, Cohen’s d = 0.79), and a lower MH score than the control group (60.2 ± 7.8 vs. 65.9 ± 8.2, p = 0.032, Cohen’s d = 0.71). In terms of the thickness of the anterior talofibular ligament and calcaneofibular ligament, the research group had thinner ATFL (1.78 ± 0.21 vs. 2.05 ± 0.24 mm, p < 0.001, Cohen’s d = 1.19) and CFL (1.32 ± 0.09 vs. 1.41 ± 0.08 mm, p < 0.001, Cohen’s d = 1.06) than the control group. Conclusion Musculoskeletal ultrasound observation of Jingshang Gao treatment for lateral ankle sprains has shown promising results in relieving pain, improving function, and promoting ligament healing. These findings suggest potential benefits of this treatment approach, though randomized controlled trials are needed for definitive efficacy assessment. Clinical trial number Not applicable.